Early Complications in Kidney Donors and Course of Health-related Quality of Life 12 mo After Donation: An Analysis of the Swiss Organ Living-Donor Health Registry - Charlotte Brügger, MS; Zoé Hunkeler, MS; Matthias Diebold, MD; Joana Krättli, MD; Irene Geiger, Lic Phil; Caroline Wehmeier, MD; Thomas Wolff, MD; Bruno Vogt, MD; Federico Storni, MD; Dela Golshayan, MD, PhD; Tobias Zingg, MD; Sophie de Seigneux, MD; et al. (Transplantation Direct)
Background. Since 1998, the Swiss Organ Living-Donor Health Registry (SOL-DHR) has recorded peri- and postoperative complications of living kidney (LK) donors, as reported by all Swiss transplant centers and has collected follow-up data prospectively. Methods. We analyzed the early complications of 2379 consecutive individuals who donated a kidney between January 1998 and June 2022 and assessed their health-related quality of life (HRQoL) 1 y after donation. Results. In total, 447 early complications in 404/2379 LK donors (17.0%) were reported to the SOL-DHR. The frequency of donors with major complications (ie, Dindo-Clavien classification 3/4) was 2.4%. In total, 31 donors needed reoperation, and in 13/31 (42%), donors reoperation was necessary because of bleeding complications. Independent risk factors for major early complications were older donor age (P = 0.005) and type of surgical approach (ie, the laparoscopic retroperitoneal compared with laparoscopic transabdominal surgery; P = 0.01), but not sex. We observed a U-shaped association of body mass index, where very low/high body mass indexes had higher odds of major early complications, without reaching statistical significance. Although HRQoL was affected by kidney donation, 96.5% of donors indicated that they would donate their kidney again. The only independent risk factor for low HRQoL based on mental health scores was worsening EB after living kidney donation (P < 0.0001). Conclusions. Overall, living kidney donation is a safe procedure, however, donor age and type of surgical approach affect the risk of complications. A decline in emotional bonding with the recipient after donation may worsen the quality of life of the donor.